The role of glucose metabolism and insulin resistance in cardiac remodelling induced by cigarette smoke exposure - Azevedo, Paula Schmidt [UNESP]; Polegato, Bertha F. [UNESP]; Paiva, Sergio [UNESP]; Costa, Nara; Santos, Priscila [UNESP]; Bazan, Silmeia [UNESP]; Fernandes, Ana Angelica Henrique [UNESP]; Fabro, Alexandre; Pires, Vanessa [UNESP]; Tanni, Suzana E. [UNESP]; Leal Pereira, Filipe [UNESP]; Lo, Angelo [UNESP]; et al. (Wiley, 2021)
The aim of this study is to evaluate whether the alterations in glucose metabolism and insulin resistance are mechanisms presented in cardiac remodelling induced by the toxicity of cigarette smoke. Male Wistar rats were assigned to the control group (C; n = 12) and the cigarette smoke-exposed group (exposed to cigarette smoke over 2 months) (CS; n = 12). Transthoracic echocardiography, blood pressure assessment, serum biochemical analyses for catecholamines and cotinine, energy metabolism enzymes activities assay; HOMA index (homeostatic model assessment); immunohistochemistry; and Western blot for proteins involved in energy metabolism were performed. The CS group presented concentric hypertrophy, systolic and diastolic dysfunction, and higher oxidative stress. It was observed changes in energy metabolism, characterized by a higher HOMA index, lower concentration of GLUT4 (glucose transporter 4) and lower 3-hydroxyl-CoA dehydrogenase activity, suggesting the presence of insulin resistance. Yet, the cardiac glycogen was depleted, phosphofructokinase (PFK) and lactate dehydrogenase (LDH) increased, with normal pyruvate dehydrogenase (PDH) activity. The activity of citrate synthase, mitochondrial complexes and ATP synthase (adenosine triphosphate synthase) decreased and the expression of Sirtuin 1 (SIRT1) increased. In conclusion, exposure to cigarette smoke induces cardiac remodelling and dysfunction. The mitochondrial dysfunction and heart damage induced by cigarette smoke exposure are associated with insulin resistance and glucose metabolism changes.
Keywords: cardiac remodelling; cigarette smoke; glucose metabolism; heart failure; ventricular remodelling